2014
DOI: 10.1080/17518253.2014.923518
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquid modification of zeolite and its removal of chromate from water

Abstract: 2014) Ionic liquid modification of zeolite and its removal of chromate from water, Green Chemistry Letters and Reviews, 7:2,[191][192][193][194][195][196][197][198] This study focused on using imidazolium of different chain lengths to modify the negatively charged zeolite. The modification involves a cation exchange process of the organic cations of ionic liquids (ILs) for the alkali and alkaline earth elements on zeolite surfaces. X-ray diffraction analyses revealed that the uptake of ILs was on the external… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The MO sorption on ILCZ modified to 1.0 and 2.0 ECEC followed the Langmuir type isotherm [35], similar to MO sorption on HDTMAmodified zeolites [24] and chromate sorption on the same type of ILCZ [36] (Fig. 2):…”
Section: Mo Sorption Isothermmentioning
confidence: 83%
See 3 more Smart Citations
“…The MO sorption on ILCZ modified to 1.0 and 2.0 ECEC followed the Langmuir type isotherm [35], similar to MO sorption on HDTMAmodified zeolites [24] and chromate sorption on the same type of ILCZ [36] (Fig. 2):…”
Section: Mo Sorption Isothermmentioning
confidence: 83%
“…Similarly, the uptake of chromate on the same type of ILCZ was also attributed to surface anion exchange [36]. Due to the negative charges of MO, the sorption of MO by ILCZ would conceivably follow the same mechanism.…”
Section: Mo Sorption Isothermmentioning
confidence: 97%
See 2 more Smart Citations
“…23 The surface active properties of ILs were used for the modication of the zeolite surface to enhance the adsorptive removal of anionic contaminants such as chromate from water. 24 Pino et al proposed the application of the 1-hexadecyl-3-methylimidazolium bromide micellar solution for the extraction of the polycyclic aromatic hydrocarbons from sediments. 25 It was revealed that ILs cannot be considered as only common cationic surfactants.…”
Section: Introductionmentioning
confidence: 99%